Access to Justice for Women Litigants in Family Courts Vis-à-Vis Prospect of a Virtual Court System: A Post- Pandemic Study With Special Reference to the Family Court in Ahmedabad District of Gujarat, India - Saxena, Parkhi (Kathmandu School of Law Review, 2022)
The COVID-19 pandemic has deeply affected the way Indian courts function and has disrupted the normal course of adjudication. While the higher judicial bodies in India such as the Supreme Court and High Courts were quick to adapt to the new norm, this was not the case for the courts at the lower rung of the hierarchy. Family Courts, where matrimonial disputes related to adoption, maintenance and divorce are adjudicated, was not an exception to this. Lockdown halted physical hearings which impacted recourse to access of Court and facilities provided to litigants. Prolonged lockdown periods have led to the suspension of case hearings which has led to several hassles for both the women litigants seeking alimony and maintenance in matrimonial cases, as well as the registered advocates practising before the family courts. The fate of these cases, along with the pending cases in family courts, remains undecided. This is a very worrisome situation, especially for women litigants whose survival depends upon the speedy resolution of cases. Through this research paper, the researcher aims to explore the current scenario at the family courts of India and the level of severity of pending cases which might have hampered the justice delivery mechanism through analysis of statistics and interviews with stakeholders. This paper also aims to navigate the possibilities of introducing a virtual court system in India in order to help the litigants who faced financial and other losses during the suspension of court hearings.